Fate of de-functioning ileostomy after left colon and rectal cancer resection: observation from a single unit of a cancer hospital. - Lamichhane, Deep; Suwal, Suraj; Rana, Resham; Shrestha, Rishikesh Narayan (Nepalese Journal of Cancer, 2023)
Background: De-functioning ileostomy (DS) has been shown to reduce rate of anastomotic leak after left colon and rectal cancer resection and can avoid consequences of leak with its morbidity and possible mortality. Externalisation of bowel is not easily appreciated; patients always inquire about the timing of closure and not all stomas are closed. The aim of the study is to assess the timing of stoma closure and the reasons for stoma becoming permanent. Methods: Patients who underwent surgery for left colon and rectal cancer with de-functioning stoma from April 2019 to May 2022 in single unit of Bhaktapur Cancer Hospital, were assessed regarding timing of stoma closure. We have made a policy of stoma closure after completion of adjuvant therapy. De-functioning stoma that was not reversed at follow up were assessed regarding reason for it becoming permanent. Results: Forty-two patients underwent de-functioning stoma during the study period; 30 after rectal resection, 2 after pouch creation, 6 after anterior resection and 4 after left hemicolectomy. Twenty-eight (77%) stomas were closed, 5 are receiving adjuvant treatment. Closure was not done in 8 patients; 5 due to recurrence of disease; 1 due to patient wish, 2 deaths occurred prior to closure, one due to COVID-19 and another due to acute myocardial infraction. One patient with multiorgan resection died within 30 days of surgery due to other medical cause. The median time of stoma closure after completion of adjuvant treatment is 8 weeks, IQR (7-10). Patients had to stay with stoma for a median period of 6months, IQR (5-8). The median time for discharge after stoma reversal is 9 days, IQR (7-10). There were 4 Grade II Clavien-Dindo complications after stoma closure. Conclusion: Seventy- seven percent of patients with DS underwent closure in our series. Recurrence was the most common cause for it becoming permanent.